Italian migration policy: Changes and effects - Dudała, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The phenomenon of Italian migration is characterized by a clear caesura, which makes Italy a country with a long history of emigration and a much shorter experience of immigration. The mid-1970s are considered a breakthrough, when the zero-migration balance was recorded for the first time. The growing wave of arriving foreigners forced the rulers to change the current immigration policy, which rarely responded to the needs of both foreigners and citizens of the Republic.
Keywords: Italian political system; migration policy; migration history; theories of migration; migration crisis